Improving test team performance through an Episodic Organizational Change implementation: A case study replication and extension - Lima, Rayfran Rocha; Barros, Margefson; Castro, Miguel; Rocha, Ana Carolina Oran; Silva, Williamson; França, César (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
CONTEXT: Despite using organizational change interventions as adaptive mechanisms to meet external and internal demands, the software industry still faces challenges in implementing effective team restructuring and reorganizing their projects to maintain or improve the productivity and quality of their activities. GOAL: This paper presents the analysis of an Episodic Organizational Change (EOC) implemented in a matrix company in the software industry that culminated in the restructuring and reorganization of a multitasking test team responsible for ensuring coverage of different test scopes demanded by several projects simultaneously. METHOD: To compare and extend the findings regarding the implementation process of EOCs in the software industry, we replicated a case study that analyzed the motivations, action plan, critical success and failure factors, positive and negative impacts, lessons learned, and suggestions for improvements. RESULTS: The experience gained in this replication suggests that the steps and elements analyzed in this case study can become an EOC analysis process applied in the software industry. Compared to the original case study, the results of this replication corroborate with the motivations, goals, action plan implementation approach, and positive results. However, they diverge from generated negative results. Besides, they expand the findings related to critical factors. Finally, they suggest a pattern in the life cycle of this type of intervention. CONCLUSION: The findings substantiate that the implementation of EOCs that impact the dynamics of teams involved in the development of software projects directly influences the productivity and quality of their deliveries. These results underscore organizations’ need for a careful and diligent approach in planning, managing, and implementing these interventions. The analysis of implemented EOCs can enhance the efficiency of this type of intervention, mitigating risks, seizing opportunities, and reducing the occurrence of failures.